Screening of salinity tolerant rice cultivars at seedling stage - Tharani, T.; Suvanthini, S.; Thirukkumaran, G. (University of Jaffna, 2015)
Rice is the staple food for more than a billion people worldwide, which includes twenty million people in Sri Lanka. Currently about 100,000 hectares of paddy lands in Sri Lanka are affected by salinity which limiting the crop production in worldwide. Therefore selection of rice cultivars which are tolerant to salinity is an important requirement for paddy cultivation in Sri Lanka too. In this study fifteen rice cultivars Masuran, Poththalai, Kahamala, Puspharaga, Heteda wee, Beheth heenati, Rathkandu, Suwandel, Dickwee, Kahawanu, Weeda heenati, Kirinaran, Rath suwandel, Rathdel and Godaheenati were collected from the Anuradhapura district to screen the salinity tolerant rice cultivars. To fix the treatments, soil samples were collected from different places in Jaffna district and the highest salinity 154μs/cm and lowest salinity 51.6μs/cm were recorded by using electrical conductivity meter. The salinity range was selected from 50 -155 μs/cm. From this preliminary study, five treatments 0, 50, 85, 120 and 155 μs/cm were selected and maintained by adding different concentration of salt solution in sixty pots. Seed germination percentage under different treatments and seedling height, shoot length, flag leaf width, flag leaf length were measured at 20, 25, 30, 35 and 40 days after planting. Complete randomized design was used to analyze the agronomic characters of cultivars and the mean was separated by DMRT. All the results were analyzed by using SAS statistical package, version 8.0. Germination percentage of the tested rice cultivars were not significantly different from the control at all salinity levels tested in this experiment except Beheththeenati and Dick.wee cultivars. Flag leaf length and girth length of all cultivars increased with increasing salt level. Plant height